2021
DOI: 10.7759/cureus.12870
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pregabalin to Decrease Postoperative Pain in Microdiscectomy: A Randomized Clinical Trial

Abstract: Purpose The purpose of this study is to compare the effect of pregabalin in reducing the neuropathic pain in postoperative patients who have undergone single-level microdiscectomy for prolapsed intervertebral lumbar disc. Methods A randomized control clinical trial was conducted from June 2018 to April 2020 in three campuses Dr. Ziauddin University Hospital, Karachi, by two spinal surgeons. This study included 84 patients who underwent either emergency or elective microdiscecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Our network meta-analysis included 27 RCTs with a total of 1861 patients (median age, 45.99 years [range, 20.00-70.00 years]; 802 women [43.1%]) including 777 patients who used placebo, included in the analysis . The network graphs are presented in Figure 2 and eFigure 1 in Supplement 1, and the main characteristics of the included studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our network meta-analysis included 27 RCTs with a total of 1861 patients (median age, 45.99 years [range, 20.00-70.00 years]; 802 women [43.1%]) including 777 patients who used placebo, included in the analysis . The network graphs are presented in Figure 2 and eFigure 1 in Supplement 1, and the main characteristics of the included studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our network meta-analysis included 27 RCTs with a total of 1861 patients (median age, 45.99 years [range, 20.00-70.00 years]; 802 women [43.1%]) including 777 patients who used placebo, included in the analysis. 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 The network graphs are presented in Figure 2 and eFigure 1 in Supplement 1 , and the main characteristics of the included studies are reported in Table 1 . The included studies were conducted in Asia (21 studies; 1528 patients), 25 , 27 , 28 , 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 47 , 48 , 49 , 50 the US (1 study; 86 patients), 43 and Europe (5 studies; 247 patients).…”
Section: Resultsmentioning
confidence: 99%